New Advances in Intelligent Decision Technologies : Results of the First KES International Symposium IDT'09 - Nakamatsu, Kazumi; Phillips-Wren, Gloria; Jain, Lakhmi C.; Howlett, Robert J. (Array, 2009)
Annotation